The D2 receptor is critical in mediating opiate motivation only in opiate-dependent and withdrawn mice - Dockstader, Colleen L. (2001)
According to the dual systems model for opiate reward, dopamine mediates opiate motivation when an animal is in a deprived motivational state (i.e. opiate-dependent and in withdrawal) and not when an animal is in a nondeprived state (i.e. previously drug-naive). To determine the role of the D2 dopamine receptor subtype in mediating opiate motivation, we examined the behaviour of N5 congenic D2 receptor knockout mice and their wild-type siblings in opiate-naive and opiate-dependent and withdrawn place conditioning paradigms. Opiate-naive D2 receptor knockout mice demonstrated acquisition of morphine-conditioned place preference but failed to acquire place preference when conditioned in the deprived state. We propose that D2 receptor function is critical in mediating the motivational effects of opiates only when the animal is in an opiate-dependent and withdrawn motivational state. These findings also underscore the important influence of the genetic background to a given phenotype, as evidenced by the observation that increasing the allelic contribution from the 129/SvJ strain abolishes morphine place preference in C57BL/6 wild-type mice.